Macrophytes from some high Andean lakes of Ecuador and their low potential as bioindicators of eutrophication - Kiersch, Benjamin; Mühleck, Ralf; Gunkel, Günter (Revista de Biología Tropical, 2004)
The occurrence of macrophyte in three high Andean lakes of Ecuador, Lago San Pablo, Laguna La Mica and Lago Cuicocha was recorded in 5-9 transects per lake. The first two lakes are eutrophic, the third is an extremely oligotrophic caldera lake. The dominant species in eutrophic lakes are Ceratophyllum demersum, Myriophyllum quitense, Potamogeton illinoensis, P. striatus and Elodea matthewsii. In the oligotrophic lake P. pectinatus, P. illinoensis, and the Characeae Chara rusbyana, Ch. globularis and Nitella acuminata occur. The maximum depth of the macrophyte’s presence can be used as an indicator of the trophic state, ranging from about 5 m in Mica to 35 m in Cuicocha. The bioindication value of the macrophyte species in these high Andean lakes is low, because few species occur and because some of them are not specific to environmental conditions.